Development of students' knowledge about didactics during their first year of the master's programme in didactics. Issue 4 (3rd July 2016) - Holmqvist Olander, Mona
Abstract: In this study, I reflect critically on my own experiences as a university teacher of students' expressed knowledge about the academic subject of didactics at the beginning and end of their first semester as students in the Master's Programme in Didactics. My reflections are made using a phenomenographic approach to learning, which regards learning as a qualitatively deeper and different way of understanding content. The results of the study are expected to deepen my understanding of knowledge expressed about didactics in two different student groups, and give insight on what is critical for knowledge development in higher education. The first course design consisted of 12 lectures in total by 12 different teachers representing different fields of didactics, such as general didactics and subject-based didactics in different specializations. The second course design consisted of eight seminars where course literature about didactics was discussed, together with three seminars in smaller groups wherein the students in each specialization of didactics met. A comparison between the groups is made, based on a qualitative analysis of the responses on an open question before and after the first semester forms the basis of my own reflections. The analysis aims to establish in what way the students' explanations of didactics might have changed during the courses, and if there are differences in this development which could be explained by differences in course design. In the first student group, 10 students (in-service teachers) answered both questionnaires, and 11 students in the second group answered both questionnaires.